Extracellular transglutaminase-2, nude or associated with astrocytic extracellular vesicles, modulates neuronal calcium homeostasis. (September 2022) - Tonoli, Elisa; Verduci, Ivan; Gabrielli, Martina; Prada, Ilaria; Forcaia, Greta; Coveney, Clare; Savoca, Maria Pia; Boocock, David J.; Sancini, Giulio; Mazzanti, Michele; Verderio, Claudia; Verderio, Elisabetta A.M.
Abstract: We have uncovered a novel role for astrocytes-derived extracellular vesicles (EVs) in controlling intraneuronal Ca 2+ concentration ([Ca 2+ ]i ) and identified transglutaminase-2 (TG2) as a surface-cargo of astrocytes-derived EVs. Incubation of hippocampal neurons with primed astrocyte-derived EVs have led to an increase in [Ca 2+ ]i, unlike EVs from TG2-knockout astrocytes. Exposure of neurons or brain slices to extracellular TG2 promoted a [Ca 2+ ]i rise, which was reversible upon TG2 removal and was dependent on Ca 2+ influx through the plasma membrane. Patch-clamp and calcium imaging recordings revealed TG2-dependent neuronal membrane depolarization and activation of inward currents, due to the Na + /Ca 2+ -exchanger (NCX) operating in the reverse mode and indirect activation of L -type VOCCs, as indicated by VOCCs/NCX pharmacological inhibitors. A subunit of Na + /K + -ATPase was selected by comparative proteomics and identified as being functionally inhibited by extracellular TG2, implicating Na + /K + -ATPase inhibition in NCX reverse mode-switching leading to Ca 2+ influx and higher basal [Ca 2+ ]i . These data suggest that reactive astrocytes control intraneuronal [Ca 2+ ]i through release of EVs with TG2 as responsible cargo, which could have a significant impact on synaptic activity in brain inflammation. Graphical Abstract: ga1 Highlights: Primed astrocytes-derived EVs control neuronal [Ca 2+ ]i via TG2 as a surface-cargo. Extracellular TG2 increases basal [Ca 2+ ]i in hippocampal neurons and brain slices. TG2 mediates Na + /K + -ATPase inhibition, inducing VOCCs opening and NCX reverse mode. Astrocytic EVs could affect synaptic activity in brain inflammation via TG2 cargo.